Revision hip arthroplasty by Waldemar Link custom-made total hip prosthesis - Medenica Ivica; Luković Milan; Radoičić Dragan (Vojnosanitetski Pregled)
Background. The number of patients undergoing hip arthroplasty revision is constantly growing. Especially, complex problem is extensive loss of bone stock and pelvic discontinuity that requires reconstruction. Case report. The paper presented a 50-year old patient, who ten years ago underwent a total cement artrhroplasty of the left hip. A year after the primary operation the patient had difficulties in walking without crutches. Problems intensified in the last five years, the patient had severe pain, totally limited movement in the left hip and could not walk at all. Radiographically, we found loose femoral component, massive loss of bone stock of proximal femur, acetabular protrusion and a consequent pelvic discontinuity. Clinically, a completely disfunctional left hip joint was registered (Harris hip score - 7.1). We performed total rearthroplasty by a custom- made Waldemar Link total hip prosthesis with acetabular antiprotrusio cage and compensation of bone defects with a graft from the bone bank. A year after the operation, we found clinically an extreme improvement in Harris hip score - 87.8. Radiographically, we found stability of implanted components, a complete graft integration and bone bridging across the site of pelvic discontinuity. Conclusion. Pelvic discontinuity and massive loss of proximal femoral bone stock is a challenging and complex entity. Conventional prostheses cannot provide an adequate fixation and stability of the hip. Application of custom-made prosthesis (measured specifically for a patient) and additional alografting bone defects is a good method in revision surgery after unsuccessful hip arthroplasty with extensive bone defects.